2013
DOI: 10.1126/science.1230593
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Mapping of Mitochondria in Living Cells via Spatially Restricted Enzymatic Tagging

Abstract: Microscopy and mass spectrometry (MS) are complementary techniques: the former provides spatiotemporal information in living cells, but only for a handful of recombinant proteins, while the latter can detect thousands of endogenous proteins simultaneously, but only in lysed samples. Here we introduce technology that combines these strengths by offering spatially- and temporally-resolved proteomic maps of endogenous proteins within living cells. The method relies on a genetically-targetable peroxidase enzyme th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
1,395
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,124 publications
(1,442 citation statements)
references
References 53 publications
37
1,395
4
6
Order By: Relevance
“…NSUN3 was suggested to localise to mitochondria (Rhee et al , 2013); however, the target spectrum and biological function of the protein have remained unknown. To confirm the mitochondrial localisation of NSUN3, we generated a HEK293 cell line stably expressing NSUN3‐GFP from a tetracycline‐inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
“…NSUN3 was suggested to localise to mitochondria (Rhee et al , 2013); however, the target spectrum and biological function of the protein have remained unknown. To confirm the mitochondrial localisation of NSUN3, we generated a HEK293 cell line stably expressing NSUN3‐GFP from a tetracycline‐inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
“…ucsd.edu. 1 To whom correspondence may be addressed. Email: clchen@genetics.med.harvard.edu or perrimon@receptor.med.harvard.edu.…”
Section: Significancementioning
confidence: 99%
“…Recently, a method based on an engineered ascorbate peroxidase (APEX) has been developed and shown to function in cultured mammalian cells for proteomic mapping (1). Upon activation, the APEX enzyme turns a biotin-phenol substrate into a highly reactive radical that covalently tags neighboring proteins on electron-rich amino acids such as tyrosine.…”
mentioning
confidence: 99%
“…The enzyme receiving CPgenIII, coproporphyrinogen oxidase (CPOX), is anchored on the mitochondrial matrix with the active site in the intermembrane space [62]. ABCB6 was proposed to be responsible for transporting CPgenIII across the mitochondrial outer membrane [63].…”
Section: Transport Of Heme Synthesis Intermediatesmentioning
confidence: 99%
“…The product of CPOX, protoporphyrinogen IX (PPgenIX), is then converted into PPIX by protoporphyrinogen oxidase (PPOX), which forms a complex with the final enzyme FECH in the mitochondrial matrix [62,65,66]. A recent report showed that PPgenIX may be transported to PPOX by transmembrane protein 14C (TMEM14C) [67].…”
Section: Transport Of Heme Synthesis Intermediatesmentioning
confidence: 99%